The Influence of ISMUBA Teacher Teaching Creativity on Student Motivation During the COVID-19 Period at SMP Muhammadiyah 1 Yogyakarta - Tumin Tumin; Sifha Eka Marvianita (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This research aimed to find out the creativity of ISMUBA (Al-Islam, Kemuhammadiyahan, and Arabic Language) teachers at SMP Muhammadiyah 1 Yogyakarta, to find out the learning motivation of students Grade VIII at SMP Muhammadiyah 1 Yogyakarta, and to identify the creativity of ISMUBA teachers in triggering learning motivation during Covid-19. The research used the correlational method with a descriptive quantitative approach. The data analysis technique was by the linearity test and simple linear regression test. The subjects of this study were the Grade VIII students of SMP Muhammadiyah 1 Yogyakarta using random sampling with 141 students. The results were: (1) the level of teaching creativity of ISMUBA teachers at SMP Muhammadiyah 1 Yogyakarta was in an appropriate category, (2) the level of student learning motivation at SMP Muhammadiyah 1 Yogyakarta is also in an appropriate category, and (3) there is a positive influence of teaching creativity on the learning motivation of Grade VIII students during Covid-19 at SMP Muhammadiyah 1 Yogyakarta. Thus, teachers’ creativity in teaching is necessary to improve student learning motivation.